Assembly Automation Technology of the Stand Type Transformer Using Power System Gripper Cable. Issue 3 (July 2021) - Pan, Peifeng; Yang, Zhiyi; Li, Longda; Jin, Xinsheng; Wu, Tao
Abstract: The cold crimping process of the lead wire of the vertical transformer of the clamp cable is a commonly used manufacturing method in the current transformer manufacturing process. Its advantages are: clean, simple, reliable, and convenient, which satisfies the manufacturing needs of high-voltage electrical products. However, due to the diversity of the lead cross-sectional area, in actual operation, it is often necessary to fill between the lead and the terminal, and there are many optional specifications for the filling line, which may easily lead to inconsistent filling methods and unclear filling standards. Aiming at a kind of vertical transformer primary winding structure and primary cable lead assembly automation research. The improved cold crimping of the lead includes two parts: the tightening and rounding of the lead and the filling of the lead copper tube as the preparatory process before the cold crimping. The post-assembly paper uses machine learning algorithms to simulate and model the wiring reliability of the connected vertical transformer, and evaluate its assembly automation level. The research results found that the wiring method proposed in the paper can improve the reliability of the wiring and the assembly efficiency is higher.